2014
DOI: 10.1111/epi.12623
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive profile of occipital lobe epilepsy and the selective association of left temporal lobe hypometabolism with verbal memory impairment

Abstract: SUMMARYWe investigated the cognitive profile of structural occipital lobe epilepsy (OLE) and whether verbal memory impairment is selectively associated with left temporal lobe hypometabolism on [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET). Nine patients with OLE, ages 8-29 years, completed presurgical neuropsychological assessment. Composite measures were calculated for intelligence quotient (IQ), speed, attention, verbal memory, nonverbal memory, and executive functioning. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Two recent meta-analyses that examined data from nearly 2000 cases of low-level occupational OP exposures reported significant decrements in working memory, visual memory, attention, psychomotor speed, executive function, and visuospatial function relative to non-exposed controls (Ismail et al, 2012; Ross et al, 2013). Notably, these cognitive processes have been linked with integrity of the frontal (Alvarez and Emory, 2006; Beyer and Krishnan, 2002; Corbetta and Shulman, 2002; Ester et al, 2015; Kochunov et al, 2010), parietal (Corbetta and Shulman, 2002; Ester et al, 2015), and occipital (Knopman et al, 2014) cortex, where we found significant, inverse associations between GM volume and the frequency of hearing chemical alarms sound in theater.…”
Section: Discussionmentioning
confidence: 66%
“…Two recent meta-analyses that examined data from nearly 2000 cases of low-level occupational OP exposures reported significant decrements in working memory, visual memory, attention, psychomotor speed, executive function, and visuospatial function relative to non-exposed controls (Ismail et al, 2012; Ross et al, 2013). Notably, these cognitive processes have been linked with integrity of the frontal (Alvarez and Emory, 2006; Beyer and Krishnan, 2002; Corbetta and Shulman, 2002; Ester et al, 2015; Kochunov et al, 2010), parietal (Corbetta and Shulman, 2002; Ester et al, 2015), and occipital (Knopman et al, 2014) cortex, where we found significant, inverse associations between GM volume and the frequency of hearing chemical alarms sound in theater.…”
Section: Discussionmentioning
confidence: 66%
“…For example, juvenile myoclonic epilepsy seems to be characterized by executive dysfunction [5]; short-term visuospatial memory dysfunction, executive dysfunction and frontal lobe dysfunction have been reported for Unverricht-Lundborg disease [6,7]; language dysfunction has been reported in Landau-Kleffner syndrome [8]; and poor language acquisition and visuospatial defects have been reported in Dravet syndrome [9] and Rett syndrome [10]. Even supposedly 'benign' epilepsies, such as benign epilepsy of childhood with centrotemporal spikes [11] or benign occipital epilepsy [12], seem to be characterized by a specific pattern of cognitive dysfunction.…”
Section: Epilepsy-related Variablesmentioning
confidence: 99%
“…In patients with occipital-lobe epilepsy, poorer verbal memory and executive function were associated with left temporal lobe hypometabolism (Knopman et al, 2014). Left mesial temporal metabolism correlated with anterograde and retrograde memory in patients with transient epileptic amnesia (Mosbah et al, 2014).…”
Section: Positron Emission Tomographymentioning
confidence: 99%